Care and Relatedness among Rural Mapuche Women: Issues of Cariño and Empathy. (September 2017) - Murray, Marjorie; Bowen, Sofía; Verdugo, Marisol; Holtmannspötter, Jona
Abstract: Based on ethnographic fieldwork in the Araucanía region of Chile, this article analyzes the caring practices of rural Mapuche women through relatedness, investigating how the study of mutual care illuminates the acknowledgment of sociality and personhood. Recounting concrete daily practices of mutual care— ayuda (help), estar atenta (being aware), and estar ahí (being there)—we examine the enactment and narratives of what these women label cariño, or affection. We argue that these women's caring practices and sense of cariño are coherent with the acknowledged volitional and autonomic features of Mapuche personhood. We also claim that paying specific attention to cariño provides novel insight for an understanding of rural Mapuche women's personhood. Cariño stands for what is considered empathy in different societies, in which feelings and actions related to empathy and empathy‐like phenomena are indistinguishable. We hope to contribute to the study of mutual care in everyday life. [care, women, Mapuche, autonomy, empathy] Basándose en trabajo de campo etnográfico en la Región de la Araucanía en Chile, este artículo analiza las prácticas de cuidado de mujeres Mapuche, investigando cómo el estudio del cuidado mutuo ilumina el conocimiento de la socialidad y el ser‐persona. Profundizando en prácticas cotidianas de cuidado mutuo – ayuda, estar alerta y estar ahí ‐ examinamos acciones y narrativas de lo que estas mujeres denominan cariño o afecto. Argumentamos que las prácticas de cuidado de estas mujeres y su sentido de cariño son coherentes con aspectos volitivos y de autonomía de la persona Mapuche. También afirmamos que prestar atención al cariño proporciona una visión novedosa para comprender el ser‐persona de las mujeres Mapuche rurales. Cariño corresponde a lo que distintas sociedades consideran empatía, en las que sentimientos y acciones relativas a la empatía y fenómenos de tipo empático son indistinguibles. Esperamos contribuir al estudio del cuidado mutuo en la vida cotidiana. [Palabras clave: cuidados, mujeres, Mapuche, autonomía, empatía] Auf Basis einer ethnographischen Feldforschung in der Araucanía‐Region Chiles untersucht dieser Artikel Fürsorgepraktiken von ländlich lebenden Mapuche‐Frauen als eine Form von Verbundenheit und beleuchtet damit die Frage, wie diese Praktiken zur Bestätigung von Sozialität und Personsein beitragen. Anhand von konkreten alltäglichen Fürsorgepraktiken wie ayuda (Hilfe), estar alerta (Aufmerksamsein), estar ahí (da sein) beschreiben wir die Performanz und die Narrative dessen, was diese Frauen als cariño oder Zuneigung bezeichnen. Wir argumentieren, dass die Fürsorgepraktiken dieser Frauen und ihr Verständnis von cariño mit volitionalen und autonomen Aspekten des Personseins bei den Mapuche verknüpft sind. Die Fokussierung von cariño bietet einen neuen Einblick in das Personsein ruraler Mapuche‐Frauen und führt zu einem, auch in anderen Gesellschaften verbreiteten, Verständnis von Empathie, wonach die damit verbundenen Gefühle und Handlungen nicht zu trennen sind. Diese Studie soll zu bisherigen Kenntnissen gegenseitiger Fürsorgepraktiken im alltäglichen Leben beitragen. [Schlüsselbegriffe: Fürsorge, Frauen, Mapuche, Autonomie, Empathie]